Pengembangan Sistem Informasi Monitoring Kualitas Air Berbasis IoT untuk Pengelolaan Sanitasi Pondok Pesantren - Dendy Kurniawan; Achmad Lutfiana Afifudin (Pusat Riset dan Inovasi Nasional, 2025)
The availability of clean water is a crucial factor in supporting sanitation and health in Islamic boarding schools, especially for bathing, washing, and toilet (MCK) facilities. Pondok Ma’had Al-Aqwam MAN Kendal faces poor water quality issues, such as murky water, unpleasant odors, and unsuitable acidity levels. This study aims to develop an Internet of Things (IoT)-based water quality monitoring information system to support real-time sanitation management in boarding schools. The system is designed using an ESP32 microcontroller integrated with pH, turbidity, and temperature sensors, displaying data directly through the Android-based Blynk application. It also includes an automation logic that activates the filtration pump when the pH or turbidity values fall outside the normal range. Testing results indicate that the system can accurately read and display water conditions and perform automatic re-filtration when water is deemed unfit for use. Expert and user validation yielded an average score of 90%, indicating the system is highly feasible for clean water management in boarding schools. Therefore, this system offers a practical and efficient solution for continuously monitoring and maintaining water quality.